A vertical lamellae arrangement of sub-16 nm pitch (domain spacing) in a microphase separated PS-b-PEO thin film by salt addition. Issue 27 (24th June 2015) - Ghoshal, Tandra; Ntaras, Christos; Shaw, Matthew T.; Holmes, Justin D.; Avgeropoulos, Apostolos; Morris, Michael A.
Abstract : 8 nm feature size nanopatterns have been fabricated from a symmetric polystyrene- b -polyethylene oxide BCP of low molecular weight using lithium ion addition. Abstract : Ultra-small feature size (∼8 nm domain width) nanopatterns have been achieved using a symmetric polystyrene- b -polyethylene oxide (PS- b -PEO) block copolymer (BCP) of low molecular weight (PS and PEO blocks of 5.5 and 5.3 kg mol −1 respectively). The work represents the smallest feature size attained and the first observation of a well-controlled film of a perpendicularly oriented lamellar pattern in thin film form for this system. The polymer synthesized and described herein has a value χ N (=7.7), below the expected BCP phase segregation limit of 10.5. These patterns were achieved by amplification of the effective interaction parameter ( χ eff ) of the BCP system by the addition of lithium chloride (LiCl) salt. A model where the Li + ions strongly coordinate with the PEO block without affecting the PS chain is proposed to explain the ordered self-assembly. The morphological and structural evolution for these PS- b -PEO/LiCl thin films was investigated by variation of the experimental parameters such as temperature, annealing time, salt concentrations, solution aging time, annealing solvent etc. All the experimental parameters have significant effects on the morphology, domain spacing, defectivity or surface roughness of these symmetric BCP thin films as evident from different microscopic and spectroscopic techniques. Possible hard mask applications in the area of lithography are demonstrated.